L’approche séquentielle du déséquilibre dans les modèles de stocks et de flux - Rouzier, Philippe (L'Actualité économique, 1978)
This article is concerned with those aspects of economic policy that are related to macro disequilibrium theory. Central to it is the way by which time enters the latter theory. Clower's dual hypothesis about Keynesian consumption function did not refer to time at all. Clower, Leijonhufvud and Howitt did introduce time in the so-called shopkeeper model, but they neglected the role of stocks. This article suggests the incorporation of buffer stocks in models of general disequilibrium. The method is the one used to endogenize policy reaction functions. Time and stocks are then the two poles around which a consistent view on quantitative economic policy can be formulated.